(untitled) (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
As global economic trends deepen in the international arena, the issues related to the formation of national economies and the study of macroeconomic problems of sustainable development become increasingly important. In the context of transformation changes, the theoretical justification of economic reforms implemented in the Republic of Azerbaijan, which has gained political and economic independence within the globalized world system, and the models chosen and applied for the purpose of forming the national economy, is of significant importance. In such a context, the study of the regularities and characteristics of the formation of a healthy national economy and sustainable development is among the key issues researched in the field of economics.